2022
DOI: 10.1038/s41418-022-00959-4
|View full text |Cite
|
Sign up to set email alerts
|

CRABP1-CaMKII-Agrn regulates the maintenance of neuromuscular junction in spinal motor neuron

Abstract: Cellular retinoic acid-binding protein 1 (CRABP1) binds retinoic acid (RA) specifically in the cytoplasm with unclear functions. CRABP1 is highly and specifically expressed in spinal motor neurons (MNs). Clinical and pre-clinical data reveal a potential link between CRABP1 and MN diseases, including the amyotrophic lateral sclerosis (ALS). We established a sequenced MN-muscle codifferentiation system to engineer an in vitro functional 3D NMJ model for molecular studies and demonstrated that CRABP1 in MNs contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…These novel activities of atRA were collectedly referred to as “non-canonical” and were later found to be mediated by the Cellular Retinoic Acid Binding Protein 1 (CRABP1) [ 22 ]. These CRABP1-mediated non-canonical activities of atRA were ultimately validated in careful studies of Crabp1 knockout (CKO) mice and cultures, which also revealed the physiological/disease relevance of CRABP1 [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introduction: Canonical and Non-canonical Activities Of All-...mentioning
confidence: 90%
See 4 more Smart Citations
“…These novel activities of atRA were collectedly referred to as “non-canonical” and were later found to be mediated by the Cellular Retinoic Acid Binding Protein 1 (CRABP1) [ 22 ]. These CRABP1-mediated non-canonical activities of atRA were ultimately validated in careful studies of Crabp1 knockout (CKO) mice and cultures, which also revealed the physiological/disease relevance of CRABP1 [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introduction: Canonical and Non-canonical Activities Of All-...mentioning
confidence: 90%
“…A different CRABP1-signaling complex was identified from studying deteriorated heart function of CKO mice [ 26 , 27 ], and their premature weakening in motor function [ 33 ]. The expression study confirmed CRABP1 expression in cardiomyocytes [ 26 ] (relevant to the CKO heart phenotype) and motor neurons (relevant to the CKO motor function phenotype) [ 33 ].…”
Section: Crabp1-signalsomesmentioning
confidence: 99%
See 3 more Smart Citations